2018
DOI: 10.2174/1874944501811010017
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction of Health Service Providers Working in a Public Tertiary Care Hospital of Pakistan

Abstract: Background: An effectively working health system is not possible without a satisfied workforce. Each year many dis-satisfied professionals either quit their profession or leave jobs in search of better opportunities. This is why the subject of job satisfaction has gained attention in the public health care sector and human resources in Pakistan in the recent past. This particular study was done to assess the job satisfaction of healthcare employees in the public tertiary hospital to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 12 publications
7
21
2
Order By: Relevance
“…The results of the study showed that the majority of the employees (82.7%) like the peoples who work with, 78% feel a sense of pride in doing jobs, 67.3% like their supervisors/ and 59.3% feel that their job is enjoyable. These results were supported by a study done by (Tasneem et al, 2018) in Pakistan which showed that the majority of the nurses were satisfied with their supervisors, nature of job and colleagues. The results of the study showed that more than one-third of the employees were satisfied with communication (40.7%) within the organization.…”
Section: Resultssupporting
confidence: 57%
“…The results of the study showed that the majority of the employees (82.7%) like the peoples who work with, 78% feel a sense of pride in doing jobs, 67.3% like their supervisors/ and 59.3% feel that their job is enjoyable. These results were supported by a study done by (Tasneem et al, 2018) in Pakistan which showed that the majority of the nurses were satisfied with their supervisors, nature of job and colleagues. The results of the study showed that more than one-third of the employees were satisfied with communication (40.7%) within the organization.…”
Section: Resultssupporting
confidence: 57%
“…Causes of dissatisfaction as quoted in this study were work environment, job designs, lack of personal or clinical autonomy and not being part of decision making process. 4 In Nigeria, only 11.8% of the nurses were very satisfied with their job whereas 82.4% were moderately satisfied and 5.8% were dissatisfied with their work. Further, this study revealed that the level of job satisfaction was positively associated with the level of achievements, advancement, responsibility, recognition, work itself, nursing practice environment, hospital policy, interpersonal relationship, salary, supervision and working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6 Many research studies suggest that nurses are least satisfied with their salaries 2,4,5,6 benefits, communication and conditions at work whereas more satisfied with their supervisors, nature of job and support from colleagues. 4,6 In the context of Nepal, two studies conducted in Kathmandu among nurses revealed that 80.6% 7 and 54.2% 8 of the nurses were satisfied with their job respectively. Further, these studies 7,8 revealed that the nurses job dissatisfaction was related with employees' expectations, salaries, working conditions and quality of supervision.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate regression further elaborated supplementary distress among doctors who were middle-aged, had more job experience or were undergoing training. Comparable results have been documented from Pakistan (2,7); where mainstream health service providers were satisfied with supervisors/colleagues and job description, but low salaries/benefits/rewards, communication matters, working conditions (15,19) and lack of service structure (20) abetted occupational satiety. Scientist labeled workplace as one of the most important factor to affect doctors; more satisfied being males, older, serving in preclinical/para-clinical departments and having infrequent departmental displacements/postings (21).…”
Section: Discussionmentioning
confidence: 84%
“…JSS is potentially apposite for health service personnel working in government-run facilities. Its validity and reliability are 0.70 and 0.86 Cronbach's Alpha Coefficient respectively (15). Scores 36-108, 108-144 and 144-216 meant dissatisfied, ambivalent/indecisive and satisfied respectively.…”
Section: Methodsmentioning
confidence: 99%